Regulating the charge diffusion of two-dimensional cobalt–iron hydroxide/graphene composites for high-rate water oxidation. Issue 23 (3rd June 2020) - Tang, Tang; Jiang, Wen-Jie; Yuan, Lu-Pan; Niu, Shuai; Hu, Jin-Song; Wan, Li-Jun
Abstract : The importance of charge diffusion in electrocatalysts is shown by regulating the thickness of CoFe hydroxide nanosheets on graphene. The few-layer nanosheets allow effective charge diffusion, enabling a 2000 mA cm −2 output at only 1.507 V cost in near-industrial conditions. Abstract : Although the significance of charge diffusion has been recognized in many high-performance energy devices, it has received very less attention in the design of electrocatalysts for the oxygen evolution reaction (OER), which is particularly crucial for highly active but less conductive OER electrocatalysts, such as two-dimensional metal hydroxides (MHs) with anisotropic conductivity. Herein, we report the elaborate design of a series of CoFe hydroxide nanosheets on graphene (CFH@G) composites to demonstrate the importance of charge diffusion regulation in improving the OER activity of MHs. It was discovered that the few-layer-thick CFH nanosheets lying on the graphene substrate provided an effective in-plane charge diffusion pathway, while keeping the substrate surface entirely covered by the laid nanosheets is necessary for providing sufficient active sites. The overly thick or stacked nanosheets are not favourable for charge diffusion, especially at large current outputs. By regulating the charge diffusion properties, the best-performing CFH@G-based material can deliver a steady OER current density of 2000 mA cm −2 at a cost of only 1.507 V under near-industrial conditions (6 M KOH and 60 °C). A practical water electrolyzer also demonstrated an impressive current output of 400 mA cm −2 at 1.694 V as well as a steady solar-to-hydrogen efficiency of 17.41%. These findings provide new insights into the role of charge diffusion in water oxidation and may open up an avenue for developing low-cost, stable and efficient electrocatalysts for practical water electrolysis and diverse energy devices.